DNA-mediated phase behavior of microsphere suspensions - Biancaniello, Paul L (Langmuir : the ACS journal of surfaces and colloids, 2007)
We have constructed a phase diagram for DNA-modified microsphere suspensions based on experimental and theoretical studies. The system is comprised of 1 microm red fluorescent colloids functionalized with strands of an identical oligonucleotide sequence and 1 microm green fluorescent colloids functionalized with the complementary sequence. Keeping the suspension composition and temperature fixed, the phase behavior of colloidal mixtures was studied as a function of salt and oligonucleotide concentration. We observed a colloidal fluid phase of dispersed, single particles at low salt concentrations and low DNA densities. We attribute this colloidal fluid phase to unfavorable hybridization conditions. With increasing salt or hybridizing oligonucleotide concentrations, we observed phase transitions of fluid --> fluid + aggregates --> aggregates due to an increase in duplex affinity, duplex number, or both. Computational analysis assigns a 4 kBT attraction between pairs of complementary microspheres at the destabilizing fluid --> fluid + aggregates transition